Biology of human respiratory syncytial virus: Current perspectives in immune response and mechanisms against the virus - Abayeneh Girma (Virus Research)
Human respiratory syncytial virus (hRSV) remains a leading cause of morbidity and mortality in infants, young children, and older adults. hRSV infection's limited treatment and vaccine options significantly increase bronchiolitis' morbidity rates. The severity and outcome of viral infection hinge on the innate immune response. Developing vaccines and identifying therapeutic interventions suitable for young children, older adults, and pregnant women relies on comprehending the molecular mechanisms of viral PAMP recognition, genetic factors of the inflammatory response, and antiviral defense. This review covers fundamental elements of hRSV biology, diagnosis, pathogenesis, and the immune response, highlighting prospective options for vaccine development.